Formulation and Evaluation of Physical Properties and Stability Test of Edible Film Ethanol Extract 96% Celery (Apium graveolens L) As Mouth Freshner - Winda Arsita Dewi (Fakultas Farmasi Universitas 17 Agustus 1945 Jakarta, 2019)
Edible Film preparations are transparent thin layers which are cut at a certain length and width which can dissolve immediately after contact with a small amount of water (saliva). Celery (Apium graveolens L) is one of the plants that is efficacious to overcome bad breath which has chemical substances such as flavonoids and which can function as antibacterial, besides that there are also alkaloids, phenolics, triterpenoids, steroids and glycosides. Celery was extracted by maceration using 96% ethanol followed by the characterization of celery extract. The edible film formulation of 96% celery ethanol extract was made with three formulas F1, F2, and F3 with each concentration of ethanol extract 96% celery 2.5%, 5%, and 7.5%. The results showed that 96% ethanol extract of celery can be formulated into edible film preparations because the evaluation of edible film preparations including organoleptics and morphology, uniformity in weight, thickness, surface pH of the film and disintegration time met the predetermined requirements. Edible film preparations that have good stability at 30oC and the preferred formula, namely in formula II, have the preferred taste, texture, smell and color by the panelists.Keywords: Edible film preparations, extracts, celery (Apium graveolens L)